Synthesis, characterization, molecular docking and biological activities of novel pyrazoline derivatives. Issue 6 (24th May 2019) - Turkan, Fikret; Cetin, Adnan; Taslimi, Parham; Karaman, Halide S.; Gulçin, İlhami
Abstract: In this study, synthesis of ethyl 2‐((4‐bromophenyl)diazenyl)‐3‐oxo‐phenylpropanoate1 was carried out and a series of new 3 H ‐pyrazol‐3‐ones (P1 –7 ) were synthesized from1 as well as various hydrazines. The obtained yields of the synthesized compounds were moderate (40–70%) and these compounds were confirmed by spectral data. These novel pyrazoline derivatives were effective inhibitor compounds of the human carbonic anhydrase I and II isozymes (hCAs I and II) and of the acetylcholinesterase (AChE) enzyme, with K i values in the range of 17.4–40.7 nM for hCA I, 16.1–55.2 nM for hCA II, and 48.2–84.1 nM for AChE. In silico studies were performed on the compounds inhibiting hCA I, hCA II, and AChE receptors. On the basis of the findings, the inhibition profile of the new pyrazoline compounds at the receptors was determined. Abstract : A series of new 3 H ‐pyrazol‐3‐ones (P1–7 ) were synthesized from of ethyl 2‐((4‐bromophenyl)diazenyl)‐3‐oxo‐phenylpropanoate1 . These novel pyrazoline derivatives were effective inhibitors of human carbonic anhydrase I and II (hCA I and II) and acetylcholinesterase (AChE), with K i values in the range of 17.4‐40.7 nM for hCA I, 16.1‐55.2 nM for hCA II, and 48.2‐84.1 nM for AChE.